Evaluation of psychotropic medications use among elderly with psychiatric disorders in Saudi Arabia - Abdulkarim M. Meraya; Otilia J.F. Banji; Moteb A. Khobrani; Abdulaziz Alhossan (Elsevier, 2021)
Aims: Potentially inappropriate psychotropic medications (PIPMs) prescribed to older adults with psychiatric disorders can inadvertently affect their health. The use of standards and guidelines can ensure prudent prescribing and minimize the risk of morbidities. This study assessed the pattern and prevalence of prescription of PIPMs to older individuals in outpatient psychiatric settings in Saudi Arabia, using the updated 2015 Beers criteria, as well as the probability of polypharmacy. Methods: The study was conducted in the outpatient psychiatric clinics of the only psychiatric hospital in Jazan region of Saudi Arabia. A retrospective cross-sectional review of electronic medical records was undertaken during 2018 to assess PIPM use and psychotropic polypharmacy. Descriptive statistics were generated and associations between PIPM use and baseline characteristics were assessed using multivariable logistic regression. Results: Overall, 68% of 1300 older adults received PIPMs, and 77.7% were on psychotropic polypharmacy. Amitriptyline, chlorpromazine, and trifluoperazine were extensively prescribed. Paroxetine (1.2%) and benzodiazepines were prescribed to a smaller proportion of the patients. Elderly with schizophrenia (AOR = 0.046, p < 0.001) and anxiety (AOR = 0.530, p = 0.036) were significantly less likely to have PIPMs than those with dementia. Likewise, elderly with depression and anxiety were less likely to have psychotropic polypharmacy as compared to those with dementia. Conclusion: A substantial number of the elderly received PIPMs possibly based on implicit criteria. It is therefore important to provide mental health care providers in the region with educational programs to increase their awareness of PIPMs.